2017
DOI: 10.1002/path.4934
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell and endometrioid carcinomas: are their differences attributable to distinct cells of origin?

Abstract: Endometrial epithelium is the presumed tissue of origin for both eutopic and endometriosis-derived clear cell and endometrioid carcinomas. We had previously hypothesized that the morphological, biological and clinical differences between these carcinomas are due to histotype-specific mutations. Although some mutations and genomic landscape features are more likely to be found in one of these histotypes, we were not able to identify a single class of mutations that was exclusively present in one histotype and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 57 publications
1
56
0
Order By: Relevance
“…While some high‐grade serous ovarian cancers are thought to arise from the malignant transformation of fimbria of the fallopian tube with subsequent early metastasis to the ovary, others may arise from the ovary itself . OEA is thought to arise from secretory epithelial cells that are frequently found in eutopic endometrium and ectopic endometriomas . Further, the cell of origin may predict aggressive disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While some high‐grade serous ovarian cancers are thought to arise from the malignant transformation of fimbria of the fallopian tube with subsequent early metastasis to the ovary, others may arise from the ovary itself . OEA is thought to arise from secretory epithelial cells that are frequently found in eutopic endometrium and ectopic endometriomas . Further, the cell of origin may predict aggressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the cell of origin may predict aggressive disease. For example, high‐grade OEA without endometriosis may develop from the secretory epithelial cells of the eutopic endometrium and already have a metastatic phenotype by the time it is discovered . On the other hand, OEA with concurrent endometriosis may develop from secretory epithelial of endometriomas and represent a nonmetastatic phenotype .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that 10 of the 40 concordant genes were significantly upregulated in our data (FDR = 0.05, S0 = 1) with many of them being known markers of CC including napsin A (NAPSA), annexin 4 (ANXA4) and hepatocyte nuclear factor 1-beta (HNF1B). Furthermore, cystathionine gamma-lyase (CTH) and interleukin-6 receptor subunit beta (IL6RB) – markers that have been associated with CC ( Cochrane et al , 2017; Hughes et al , 2016; Yanaihara et al , 2016) – were found to be elevated in CC compared to EMT samples. CTH was found to be significantly elevated in CC compared to EMT (p=0.01) while IL6RB was undetectable in all EMT samples but expressed in 4/6 of the CC samples.…”
Section: Resultsmentioning
confidence: 99%